ANALISIS RENCANA PEMODELAN AKSES JALAN BARU DI YOGYAKARTA (STUDI KASUS : MENGHUBUNGKAN JALAN COLOMBO DENGAN JALAN URIP SUMAHARJO) - , YUDISTIRA OKTOBARI HELIANTO P, Ir. Djoko Murwono M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Yogyakarta is one of Indonesia's major cities are directly adjacent to the district of Sleman and Bantul. Some areas to the location of center of activity can only be done through the street without any supporting alternative path. Gejayan Street, Colombo Street and Urip Sumarhajo Street are the lifeblood of transportation lines in the city center. Transport flows and high mobility in the lane gave the possibility of the region to develop quite prospective in the tourism and education sector. Of course, this also brings considerable impact on the change in the quantity of traffic flow. This script aims to model the potential opening of a new access road to a block / area zone, and how the interaction opportunities between regions, especially related to the fluency of traffic. Modeling done by trial JICA STRADA Ver.2 software. In the design of transport used four stages: trip generation models use growth factors. Distribution movement models using an analogy with the limits for a generation, while the selection mode stages using the survey results. For selection route stage is using phase equilibrium model which issued by JICA. Based on the results of data modeling can be seen that in the 5 years to come some streets value v / c ratio of 1.17, reaches greatest. In the presence of that new road, the movement flows from north to south which previously passed Demangan market will have alternative routes that pass through the new path that reduces 32% movement, from 3,295 pcu / hour (v / c ratio = 0.89) to 2,255 smp / hour (v / c ratio = 0.61). At Prof. YohanesStreet, the traffic volume will be reduced 26%, from 1,947 pcu / hour (v / c ratio = 0.79) to 1,448 pcu / hour (v / c ratio = 0.59). This is because the movement of people from UNY through the streets of Prof. Yohanes Streetbefore and then could go straight south past the new road and as the consequence, volume flow Urip Sumoharjo Street western road will increase (v / c ratio becomes 0.70 v / c ratio 0 , 76).